2002
DOI: 10.4049/jimmunol.168.6.3004
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role for T Cells in Sephadex-Induced Airway Inflammation: Pharmacological and Immunological Characterization and Molecular Biomarker Identification

Abstract: Intratracheal instillation of Sephadex particles is a convenient model for assessing the impact of potential anti-inflammatory compounds on lung eosinophilia thought to be a key feature in asthma pathophysiology. However, the underlying cellular and molecular mechanisms involved are poorly understood. We have studied the time course of Sephadex-induced lung eosinophilia, changes in pulmonary T cell numbers, and gene and protein expression as well as the immunological and pharmacological modulation of these inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 68 publications
(61 reference statements)
2
20
1
Order By: Relevance
“…These studies show the role played by eotaxin in eosinophil recruitment in the lung tissue. After Sephadex bead injection, both eotaxin and eosinophils increased in a dose-related manner in the BALF from adults, which was consistent with previous results (15,30,37). In contrast, no treatment-related changes in eotaxin were observed in our pup model.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…These studies show the role played by eotaxin in eosinophil recruitment in the lung tissue. After Sephadex bead injection, both eotaxin and eosinophils increased in a dose-related manner in the BALF from adults, which was consistent with previous results (15,30,37). In contrast, no treatment-related changes in eotaxin were observed in our pup model.…”
supporting
confidence: 82%
“…This is not consistent with a previous study (30) that showed that gene or protein expression of IFN-␥ was not increased after Sephadex bead treatment even in the adult rat lung. Unfortunately, there is no clear explanation for this difference.…”
contrasting
confidence: 47%
See 2 more Smart Citations
“…24 h after Sephadex administration; body weight was recorded followed by the removal of the heart and lungs en bloc. Next, the lungs were excised, and determination of wet lung weights along with correction for 100 g of initial body weight was performed as previously described (Belvisi et al, 2000;Haddad et al, 2002).…”
Section: Methodsmentioning
confidence: 99%